Control of synthetic microbial consortia in time, space, and composition. Issue 12 (December 2021) - Grandel, Nicolas E.; Reyes Gamas, Kiara; Bennett, Matthew R.
Abstract : While synthetic microbial systems are becoming increasingly complicated, single-strain systems cannot match the complexity of their multicellular counterparts. Such complexity, however, is much more difficult to control. Recent advances have increased our ability to control temporal, spatial, and community compositional organization, including modular adhesive systems, strain growth relationships, and asymmetric cell division. While these systems generally work independently, combining them into unified systems has proven difficult. Once such unification is proven successful we will unlock a new frontier of synthetic biology and open the door to the creation of synthetic biological systems with true multicellularity. Highlights: Single-strain systems are outpaced in efficiency and application complexity by multicellular systems. Microbial consortia have enormous potential but are difficult to control. This review breaks down control strategies into spatial, temporal, and compositional control. Researchers have utilized the partitioning of plasmids during cell division to create a version of microbial differentiation, creating daughter cells lacking plasmids by binding all copies of the plasmid of interest to each other. A bacterial adhesin toolkit composed of many distinct and orthogonal adhesin pairs enabled adhesion-driven self-assembly of several different patterns, including differential adhesion and phase separation within liquid media. Improvements in compositional control have directly enabled advancements in other areas of consortial control, such as improving plasmid maintenance and increasing the number of constituent species in a consortium.